Inhibitory properties of crude microalgal extracts on the in vitro replication of cyprinid herpesvirus 3 - Fritzsche, Stefanie; Blenk, Patrik; Christian, Juergen; Castiglione, Kathrin; Becker, Anna (Scientific Reports, 2021)

Performance of environmentally friendly, liquid-infused coatings against biofouling: evaluation of macrofouling and microbially induced corrosion in freshwater environments - Walter, Teresa; Langbein, Manuela; Blenk, Patrik; Tesler, Alexander; Prado, Lucia; Bornstein, Dan; Virtanen, Sannakaisa; Castiglione, Kathrin; Vogel, Nicolas (Journal of Materials Chemistry A, 2024)
Biofouling, caused by the attachment of micro- and macroorganisms, increases the fuel consumption of ships and compromises aquatic infrastructure, especially by microbially induced corrosion. Conventional anti-fouling strategies often rely on the release of toxic substances. Liquid-infused coatings offer an alternative strategy, which has shown promising anti-fouling performance in maritime settings. In this study, we focus on freshwater systems and investigate the performance of a set of recently developed liquid-infused coatings with low environmental impact based on sustainable or non-toxic materials and energy-efficient fabrication. We combine field studies at two freshwater bodies in Bavaria, Germany with laboratory experiments focusing on corrosion and microbial attachment under controlled conditions. Our results indicate that liquid-infused coatings with low environmental impact can show a reduction in general biofouling, mussel attachment, and corrosion rates, as well as the attachment of Thiobacillus thioparus and Pseudomonas fluorescens, organisms known to cause microbially induced corrosion.<br